Enterovirus D68 seroepidemiology in Taiwan, a cross sectional study from 2017 - Lee, Jian-Te; Shih, Wei-Liang; Yen, Ting-Yu; Cheng, Ai-Ling; Lu, Chun-Yi; Chang, Luan-Yin; Huang, Li-Min (PloS one, 2020)
Enterovirus D68 (EV-D68) was discovered in 1962 and has unique characteristics compared to the characteristics of other enteroviruses. There were few documented cases before the epidemic in the United States in 2014. The Taiwan Centers for Diseases Control also confirmed that EV-D68 has been endemic, and some cases of acute flaccid myelitis were reported in Taiwan. To understand the current EV-D68 serostatus, we performed an EV-D68 seroepidemiology study in Taiwan in 2017. After informed consent was obtained, we enrolled preschool children, 6- to 15-year-old students and 16- to 49-year-old people. The participants underwent a questionnaire investigation and blood sampling to measure the EV-D68 neutralization antibody. In total, 920 subjects were enrolled from the northern, central, southern and eastern parts of Taiwan with a male-to-female ratio of 1.03. The EV-D68 seropositive rate was 32% (26/82) in infants, 18% (27/153) in 1-year-old children, 43% (36/83) in 2-year-old children, 60% (94/156) in 3- to 5-year-old children, 89% (108/122) in 6- to 11-year-old primary school students, 98% (118/121) in 12- to 15-year-old high school students, 100% (122/122) in 16- to 49-year-old women and 100% (81/81) in 16- to 49-year-old males in 2017. Among preschool children, EV-D68 seropositivity was related to age (p for trend <0.0001), size of household ≧4 members (p = 0.037) and kindergarten attendance (p = 0.027). The seropositive rate varied among different geographic regions. EV-D68 infection was prevalent, and its seropositive rates increased with age, larger household size and kindergarten attendance among preschool children.